Application of the "Hutawabosi" Method to Reduce Learning Barriers for Students with Special Needs duringthe Pandemic - Syamsuri, Muhammad (Pinisi Journal of Education and Management, 2022)
This study aims to describe the 'Hutawabosi' method in reducing learning barriers, especially in facilitating the completion of assignments by students suspected of having special needs in learning during the pandemic. The type of research used is qualitative research in the form of case studies. The research was conducted using direct interviews with research subjects as a form of searching and direct documentation in the field. Researchers also use observation techniques as a way to complete the data that has been found. The research focuses on interventions against learning barriers for students with special needs, especially in learning during the pandemic. The results showed that the "Hutawabosi" method was able to reduce learning barriers and facilitate the completion of assignments by students suspected of having special needs. Evidenced by interviews with subject teachers and reduced complaints about assignments given to students with special needs.